Integrated agriculture-aquaculture as an alternative to improving small-scale fish production in Zambia - Hasimuna, Oliver J.; Maulu, Sahya; Nawanzi, Kundananji; Lundu, Benjamin; Mphande, Joseph; Phiri, Chisomo J.; Kikamba, Edwin; Siankwilimba, Enock; Siavwapa, Sillah; Chibesa, Moses (Frontiers in Sustainable Food Systems, 2023)
Aquaculture is a significant industry in food production, and its contribution to food and nutrition security is well acknowledged. Zambia’s aquaculture production has continued to increase significantly, thus playing a key role in supplying animal protein sources for human consumption. However, recent estimates show that 75 % of the national aquaculture production comes from large-scale commercial producers despite being by far the minority while the majority of small-scale producers contribute the remaining 25 % of the total annual production. This low production by small-scale producers is attributed to insufficient financial resources, poor management and utilization of farm resources, lack of access to competitive markets, and more recently a changing climate. In this research, we examine the viability of integrated agriculture-aquaculture (IAA) as a means for small-scale producers in Zambia to boost their aquaculture output despite the numerous obstacles they confront. In addition, the obstacles that could prevent small-scale manufacturers from adopting IAA have been emphasized. We conclude that IAA has the potential to dramatically boost small-scale aquaculture production in Zambia, but information and understanding must be improved to make it a more feasible alternative.